Transformative Education to Prepare A Generation with Strong Character - Zainuddin, Mohammad; Suhid, Asmawati; Romero Roman, A. (International Journal of Engineering and Technology, 2019)
Character education is crucial for the societyâ€™s and stateâ€™s sustainability, especially in modern and global era. It is important even more for the future of young generation which requires special attention and serious. Therefore, a holistic educational paradigm is vital to be formulated and then immediately implemented in our education world. This paper focuses on the study of how education has a central force in building students' character. The method and approach used in this paper is a philosophical approach. From the results of this study, the authors recommend that the concept of education should develop programs focusing on character and teaching values. The programs emphasize on the issue of human identity beside the development of communication skills and interpersonal relationships in performing the duties and responsibilities as a caliph on earth. Therefore, the curriculum must be compiled and structured to meet the overall objectives of education. Curriculum is actually not only verbal concerning the purpose, content, and courses, it is also a non-verbal curriculum (hidden curriculum) in form of exemplary educators or teachers (including the leader of the nation). Thus, it is the nature of teachers, educators and leaders that all words, deeds, and provisions should become a role model for others (students and community).Â Â